2019
DOI: 10.1002/ppsc.201900152
|View full text |Cite
|
Sign up to set email alerts
|

Digital Assembly of Colloidal Particles for Nanoscale Manufacturing

Abstract: From unravelling the most fundamental phenomena to enabling applications that impact our everyday lives, the nanoscale world holds great promise for science, technology, and medicine. However, the extent of its practical realization relies on manufacturing at the nanoscale. Among the various nanomanufacturing approaches being investigated, the bottom‐up approach involving assembly of colloidal nanoparticles as building blocks is promising. Compared to a top‐down lithographic approach, particle assembly exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…[ 176 ] Digital assembly of colloidal nanoparticles one by one with optical tweezers or optothermophoretic tweezers is another approach for constructing nanomaterials with sophisticated architectures. [ 177 ] Nanoscale manufacturing of colloidal directional nanoparticles, including optical nanoprinting and digital assembly, is pivotal in both scientific understanding and real applications of nanomaterials and nanodevices for directional light scattering and emission.…”
Section: Discussionmentioning
confidence: 99%
“…[ 176 ] Digital assembly of colloidal nanoparticles one by one with optical tweezers or optothermophoretic tweezers is another approach for constructing nanomaterials with sophisticated architectures. [ 177 ] Nanoscale manufacturing of colloidal directional nanoparticles, including optical nanoprinting and digital assembly, is pivotal in both scientific understanding and real applications of nanomaterials and nanodevices for directional light scattering and emission.…”
Section: Discussionmentioning
confidence: 99%
“…A key strength of magnetic field-assembly is the reversibility of the interactions, which leads to a rapid return to the disordered state when the field is removed. 54,56,211 Magnetic field has been successful applied to the manipulation and assembly of magnetic and non-magnetic colloidal particles, also taking advantage of ferrofluids, [212][213][214] as well as the assembly of soft materials, such as cyclodextrin vesicles (CDV), by incorporating magnetic NPs, 215 and to the magnetic separation. In particular, Colvin et al reported that the magnetic separation of magnetite (Fe 3 O 4 ) NPs from a solution can be accomplished at very low magnetic field gradients thanks to their aggregation, which is due to the high field gradients at the NP surfaces.…”
Section: Electric and Magnetic Fieldsmentioning
confidence: 99%
“…Certainly, this may be an optimal strategy for many devices, but to explore and expand possible applications of bottom-up technologies, physical positioning of structures must be mastered beyond the current state of the art. One method of positioning that has attracted certain attention is optical tweezing. Optical tweezing has two steps. First, a stable optical trap wherein the radiation pressure force exhibits negative feedback with respect to position on a particle must be created.…”
Section: Introductionmentioning
confidence: 99%